STEREOTYPING PEREMPUAN DALAM SUAMI-SUAMITAKUT ISTRI TRANSTV - Zamroni, Muhammad; Primadewi, Nerfita (Capture : Jurnal Seni Media Rekam, 2013)
This research describes about one of television genre programs called Suami-suamiTakut Istri.The problem is how stereotyping of woman's character in the Suami-suamiTakut Istriprogram? In addition, this research uses qualitative design and semiotic signification. From theresult,this research showed the stereotype of the woman's figure.There are particularly threestereotypes showed character, acting territory, and the relationship between men and women.Furthermore,the kinds of stereotypes among others indicate that a figure is feminine,emotional,domestic acting, and as a male sex object.Therefore, it is a proof that the sitcom Suami-suamiTakut Istri in Trans TV is not a program which empowers women because it is still on thestereotype to women.Keywords: Stereotype,sitcom,and Suami-SuamiTakut Istri